The presence of radioactive materials in soil, sand and sediment samples of Potenga sea beach area, Chittagong, Bangladesh: Geological characteristics and environmental implication - Yasmin, Sabina; Barua, Bijoy Sonker; Khandaker, Mayeen Uddin; Kamal, Masud; Abdur Rashid, Md.; Abdul Sani, Siti Fairus; Ahmed, Hossain; Nikouravan, Bijan; Bradley, David Andrew (Elsevier, 2018)
Accurate quantification of naturally occurring radioactive materials in soil provides information on geological characteristics, possibility of petroleum and mineral exploration, radiation hazards to the dwelling populace etc. Of practical significance, the earth surface media (soil, sand and sediment) collected from the densely populated coastal area of Chittagong city, Bangladesh were analysed using a high purity germanium γ-ray spectrometer with low background radiation environment. The mean activities of 226Ra (238U), 232Th and 40K in the studied materials show higher values than the respective world average of 33, 36 and 474 Bq/kg reported by the UNSCEAR (2000). The deduced mass concentrations of the primordial radionuclides 238U, 232Th and 40K in the investigated samples are corresponding to the granite rocks, crustal minerals and typical rocks respectively. The estimated mean value of 232Th/238U for soil (3.98) and sediment (3.94) are in-line with the continental crustal average concentration of 3.82 for typical rock range reported by the National Council on Radiation Protection and Measurements (NCRP). But the tonalites and more silicic rocks elevate the mean value of 232Th/238U for sand samples amounting to 4.69. This indicates a significant fractionation during weathering or associated with the metasomatic activity in the investigated area of sand collection.